Murder in Brentwood - Fuhrman, Mark. (Washington, D.C. : Regnery Pub., 1997)
Former police detective Mark Fuhrman describes his part in the investigation of the murder of Nicole Brown Simpson and Ron Goldman, his testimony in the trial, his nolo contendere plea to charges of perjury, and the effect the Simpson trial had on Fuhrman's family.
Nolo contendere -- Murder in Brentwood -- The Rockingham estate -- Costly errors -- The interrogation -- Slow-speed pursuit -- The scheme team -- Witness for the people -- The defense card -- The allegations and the facts -- Living in a fishbowl -- The judge and his wife -- The evidence -- The prosecution's case -- The murder weapon -- Hypothesis of a murder -- Marcia's case -- Darden for the defense -- Taking the stand -- Crossing the line -- Center stage -- Defending the indefensible -- The tapes -- Taking the fifth -- Closing arguments -- Verdict aftermath.
Includes index.
Keywords: Murder -- Investigation -- California -- Los Angeles; Crime scene searches -- California -- Los Angeles; Evidence, Criminal -- California -- Los Angeles; Simpson, O. J., -- 1947-2024 -- Trials, litigation, etc